6,8-Dibromo-5-hydroxy-4-oxo-2-phenyl-4H-chromen-7-yl acetate - Nallasivam, Angannan (International Union of Crystallography, 2009)
In the title compound, C(17)H(10)Br(2)O(5), the chromene ring is almost planar with minimal puckering [total puckering amplitude = 0.067 (4) Å]. The dihedral angle between chromeme ring system and phenyl ring is 3.7 (2)°. The crystal structure is stabilized by intermolecular C—H⋯O interactions and an intramolecular O—H⋯O hydrogen bond also occurs.